A self‐cured glass‐ionomer cement with improved antibacterial function and hardness. (13th August 2020) - Chen, Yong; Caneli, Gulsah; Almousa, Rashed; Hill, Kayla; Na, Sungsoo; Anderson, Gregory G.; Xie, Dong
Abstract : A novel antimicrobial dental self‐cured glass‐ionomer cement has been developed and evaluated. Alumina filler particles were covalently coated with an antibacterial polymer and blended into a self‐cured glass‐ionomer cement formulation. Surface hardness and bacterial viability were used to evaluate the modified cements. Results showed that the modified cements exhibited a significantly enhanced antibacterial activity along with improved surface hardness. Effects of antibacterial moiety content, alumina particle size and loading, and total filler content were investigated. It was found that increasing antibacterial moiety content, particle size and loading, and total filler content generally increased surface hardness. Increasing antibacterial moiety, filler loading and total filler content increased antibacterial activity. On the other hand, increasing particle size showed a negative impact on antibacterial activity. The leaching tests indicate no cytotoxicity produced from the modified cements to both bacteria and 3T3 mouse fibroblast cells.